Management regimes underpin soil carbon accrual following forest conversion to tea plantations across China - Lin Chen; Li Ruan; Yu Duan; Biao Feng; Yixuan Bai; Scott X. Chang; Teng Yang; Yowhan Son; Yuwei Yuan; Shangwen Fu; Chuan Yue; Zhongyi Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Click Chemistry-Based Quantification of Extracellular Matrix Turnover for Drug Screening and Regenerative Medicine - Annie Porter; Songshan Fan; Ying Peng; Mengxi Lv; Yilu Zhou; Abdulaziz Alanazi; Lin Han; Liyun Wang; X. Lucas Lu (Annals of Biomedical Engineering, 2026)
Purpose To develop and validate a bioorthogonal labeling approach for quantifying ECM remodeling in living cell and tissue culture systems. Methods Strain-promoted azide-alkyne (SPAAC) reactions, or copper-free click chemistry, were used to fluorescently label newly synthesized glycan and protein matrix components. ECM synthesis and degradation was quantified in cartilage explants, human mesenchymal stem cells, and SKBR3 breast cancer cells under various external stimuli, including inflammation, mechanical stimulus, and drug treatment. Results The click chemistry method reliable quantified ECM turnover across platforms. It detected reduced glycan and protein synthesis after 24-hour inflammatory challenge and enabled longitudinal tracking of ECM degradation in cartilage explants. The technique demonstrated high sensitivity, measuring increased ECM deposition by ~ 10,000 human mesenchymal stem cells in 12-hour intervals and substrate stiffness-dependent synthesis by SKBR3 cells. Additionally, the approach supported osteoarthritis drug screening by identifying compounds that mitigated inflammation-induced ECM degradation. Conclusion Compared to traditional biochemical or histological assays, the click chemistry-based technique provides higher sensitivity, reduced sample requirements, and improved temporal resolution for quantifying ECM turnover. Its versatility enables broad application in tissue engineering, regenerative medicine, disease modeling, and high-throughput drug evaluation.

Removal of microplastics in water and wastewater: prospects toward a circular economy - Van-Hiep Hoang; Minh-Ky Nguyen; Tuan-Dung Hoang; Chitsan Lin; Minh Cuong Ha; Nguyen Thi Thanh Huyen; Adnan Hussain; X. Hoan Nguyen; Woojin Chung; D. Duc Nguyen (Clean Technologies and Environmental Policy, 2026)

Addition of PRG4 to Optimize the Anti-Adhesive Properties of Tissue Barrier Seprafilm® - Ava J. Marks; Khaled A. Elsaid; Ling X. Zhang; Timmy Lin; Janette Baird; Tannin A. Schmidt; Gregory D. Jay (Annals of Biomedical Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

Beyond the check-up: how well-child exams, pediatric specialists, and provider recommendations can close HPV vaccine gaps for Chinese American Teens - Lin Zhu; Xinrui Li; Elaine Zhiqing Liu; Philip T. Siu; Shumenghui Zhai; Chun Pan; Nikki Cao; Grace X. Ma (Cancer Causes & Control, 2026)
Purpose This study aimed to identify provider- and practice-level factors influencing human papillomavirus (HPV) vaccine uptake among Chinese American (CA) adolescents. Despite increasing public health efforts, HPV vaccination rates in this population remain suboptimal, and knowledge on the link between provider/practice characteristics and vaccine uptake is limited. Methods We analyzed data from 1,272 CA adolescents (aged 13–17) using the National Immunization Survey-Teen (2015–2019) datasets. Key measures included HPV vaccine initiation and completion (based on proxy reporting and verification), accompanied by various multilevel factors: provider-level (recommendation, specialty), practice-level (facility type, vaccine acquisition, well-child exam), parent-level (mother’s education, marital status), and adolescent-level characteristics. Weighted descriptive statistics and stepwise multivariate logistic regression were used to examine associations. Results Overall, 71.22% of CA adolescents initiated at least one HPV vaccine dose, while 48.14% completed the regimen. Provider's recommendation (initiation OR = 21.50, completion OR = 8.12), having a pediatrician (initiation OR = 5.37, completion OR = 3.20), and receiving the 11–12-year-old well-child exams significantly predict both initiation and completion. Regional disparities were observed, with adolescents in the Northeast and West showing higher completion rates than those in the South. Unexpectedly, adolescents not enrolled in school and those with mothers who had less than 12 years of education or were unmarried showed higher completion rates. Conclusion Provider recommendations and pediatric care are crucial for improving HPV vaccination rates among CA adolescents. Addressing regional disparities and implementing targeted interventions, including enhanced provider training focused on culturally sensitive communication, are essential to dismantle systemic barriers and improve comprehensive vaccination coverage in this underserved population.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Overlooked synergisms of flotation organic reagents and toxic metals in water: Formation of tridentate cadmium-xanthate complexes - Lei Xiang; Qian-Wen Wang; Wen-Jun Wu; Nian-Jue Zheng; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; Qing X. Li (Water Research, 2025)

Both biotic and abiotic soil N₂O productions are lower under organic N than inorganic N deposition in a Moso bamboo forest - Wenting Jiang; Yan Wang; Yongxin Lin; Hiroko Akiyama; Yunying Fang; Tony Vancov; Shenglei Fu; Hojeong Kang; Xinli Chen; Zhengqin Xiong; Zhijie Li; Shuijin Hu; et al. (Biology and Fertility of Soils, 2025)

Perfluorooctane sulfonate (PFOS) promotes transformational transfer of antibiotic resistance genes and cross-resistance between antibiotics and PFOS - Hui Zhao; Hai-Ming Zhao; Feng Wu; Bai-Lin Liu; Hui Li; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; Ce Hui Mo; Qing X. Li (Water Research, 2025)

Adsorption of phosphorus on different substrates of constructed wetlands - X. Liu; M. Tang; C. Lin; H. Zhu; Z. Xu; H. Zhai; X. Tan (International Journal of Environmental Science and Technology, 2025)

Driving factors of summer diurnal surface thermal environment in subtropical coastal cities: a Shenzhen case study - Q. Guo; Y. Lin; S. Zhong; X. Zhang (International Journal of Environmental Science and Technology, 2025)

Comparison of indoor hydroponic plants for decarbonization and cooling performance: the field experiment of three vegetation species - G. Zhang; Q. Lin; X. Li; H. Xia; H. Li (International Journal of Environmental Science and Technology, 2025)

Retraction notice to ‘Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals’ [Sci. Total Environ., 926 (2024) 171859] - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Constraints of the paleowind directions on the paleogeography of the North China, South China and Tarim cratons during the Ediacaran Period - C. L. Hu; Z. Q. Lin; J. A. Quaye; X. B. Fu (Australian Journal of Earth Sciences, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Experimental study on macro spray, combustion and emission characteristics of biodiesel and diethyl carbonate blends - L. Zhao; X. Zhu; R. Zhao; J. Tian; D. Qian; Q. Lin (International Journal of Environmental Science and Technology, 2025)

Downregulation of A20 Expression Related to T Cells by Staphylococcal Enterotoxin A Treatment - X. Chen; Y. Yan; C. Lin; J. Yang; H. Qiu (Bulletin of Experimental Biology and Medicine, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

New astrometric positions for six Jovian irregular satellites using Gaia DR3 in 2016 — 2021 - X. Lu; Q.Y. Peng; A. Vienne; X.Q. Fang; F.R. Lin (Icarus, 2025)

Short term air pollution exposure during pregnancy and associations with maternal immune markers - C.S. Yount; K. Scheible; S.W. Thurston; X. Qiu; Y. Ge; P.K. Hopke; Y. Lin; R.K. Miller; S.K. Murphy; J. Brunner; E. Barrett; T.G. O'Connor; et al. (Environmental Research, 2024)

Fluid inclusion characteristics and mechanisms of tin mineralisation in the Jialong tin polymetallic deposits, Jiuwandashan–Yuanbaoshan, northern Guangxi, China - C-L. Meng; L-A. Bai; Z-H. Yue; S-Y. Zhou; Y. Dai; Z-H. Feng; X-J. Liu; H. Zhang; L-Z. Lin (Australian Journal of Earth Sciences, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Protective Effect of Protocatechuic Aldehyde on Cerebral Ischemia/Reperfusion Injury in Rats through Blood—Brain Barrier Protection - F. He; J. Feng; H. Sun; Y. Xu; H. Yan; X. Song; Y. Wang; X. Li; Q. Lin (Bulletin of Experimental Biology and Medicine, 2024)

Toxicity and metabolism of deoxynivalenol and its reversal by Bacillus subtilis in broiler chickens - Y. Lin; S. Wang; X. Deng; N. Liu; J. Wang (Animal Feed Science and Technology, 2024)

P21-52 Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - H. Hong; J. Li; T. Tong; X. Lin; Y. Xu; J. Lin; S. Liu; K. Luo; Z. Zhou (Toxicology Letters, 2024)

Improving the sustainability of milk production across different climate regions in China - Zhaoping Wu; Yuanyuan Du; Guofu Yang; Linshan Lin; Xiaoyu Hou; Yandong Tan; Xing Fan; Yuan Ren; Bijie Wu; Shun Liu; Scott X. Chang; Wanhong Sun; et al. (Sustainable Production and Consumption, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Review on personal protective equipment: Emerging concerns in micro(nano)plastic pollution and strategies for addressing environmental challenges - Van-Giang Le; Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Tri Quang Hung Nguyen; Nguyen K. Hue; Quoc-Minh Truong; Soon W. Chang; X. Hoan Nguyen; D. Duc Nguyen (Environmental Research, 2024)

Nonlinear contributions of surface solar brightening to maize yield gains in the US Corn Belt - H. Zhao; H. Yang; T.J. Avenson; G.F. Sassenrath; MB. Kirkham; S.W. Welch; L. Zhang; N. Wan; A.M. Nelson; P. Gowda; X. Lin (Agricultural and Forest Meteorology, 2024)

Distinct effects of canopy vs understory and organic vs inorganic N deposition on root resource acquisition strategies of subtropical Moso bamboo plants - Lin Wang; Baogang Zhang; Yunying Fang; Huajun Yin; Shenglei Fu; Scott X. Chang; Yanjiang Cai (Science of The Total Environment, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

RETRACTED: Applications of engineered biochar in remediation of heavy metal(loid)s pollution from wastewater: Current perspectives toward sustainable development goals - Thien-Khanh Tran; Loan Huynh; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Tuan-Dung Hoang; Nguyen Tri Q. Hung; X. Hoan Nguyen; S. Woong Chang; D. Duc Nguyen (Science of The Total Environment, 2024)

The spatial effect of upgrading economic development zones on regional eco-efficiency: evidence from China - Z. Zhang; X. Wei; X. Lin (International Journal of Environmental Science and Technology, 2024)

On the brink of explosion? Identifying the source and potential spread of introduced Zosterops white-eyes in North America - Devon A. DeRaad; Marlon E. Cobos; Natalie R. Hofmeister; Lucas H. DeCicco; Madhvi X. Venkatraman; Isao Nishiumi; Bailey McKay; Fa-Sheng Zou; Kazuto Kawakami; Chang-Hoe Kim; Ruey-Shing Lin; Cheng-Te Yao; et al. (Biological Invasions, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

Review of risk assessment for navigational safety and supported decisions in arctic waters - X. Yang; Z.Y. Lin; W.J. Zhang; S. Xu; M.Y. Zhang; Z.D. Wu; B. Han (Ocean & Coastal Management, 2024)

An indeterministic fractional two-stage inter-regional energy system optimization model: A case study for the Province of Shanxi, China - Y.L. Zheng; G.H. Huang; Y.P. Li; J.P. Chen; X. Zhou; B. Luo; Y.P. Fu; L.J. Lin; Z.P. Xu; W.C. Tang (Journal of Cleaner Production, 2024)

Biodegradation of polystyrene microplastics by superworms (larve of Zophobas atratus): Gut microbiota transition, and putative metabolic ways - Zhaolin Quan; Zixi Zhao; Zhimin Liu; Weijun Wang; Shunyu Yao; Huiren Liu; Xiaoqiu Lin; Qing X. Li; Hai Yan; Xiaolu Liu (Chemosphere, 2023)

Occurrence, fate, and potential risk of pharmaceutical pollutants in agriculture: Challenges and environmentally friendly solutions - Minh-Ky Nguyen; Chitsan Lin; Hoang-Lam Nguyen; Nguyen Tri Quang Hung; D. Duong La; X. Hoan Nguyen; S. Woong Chang; W. Jin Chung; D. Duc Nguyen (Science of The Total Environment, 2023)

Giant strain performance of lead-free relaxor piezoceramics through synergistic compositional and defect engineering - J. Sheng; W.P. Cao; W.L. Li; Q.R. Lin; M.L. Li; X. Hou; W.D. Fei (Chemical Engineering Journal, 2023)

DeepFlame: A deep learning empowered open-source platform for reacting flow simulations - Runze Mao; Minqi Lin; Yan Zhang; Tianhan Zhang; Zhi-Qin John Xu; Zhi X. Chen (Computer Physics Communications, 2023)

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Whole bone subcutaneous transplantation as a strategy to study precisely the bone marrow niche - Caroline C. Picoli; Patrícia Rocha Martins; Xiao Lin Casey Wong; Thamires Righi; Pedro P. G. Guimarães; Mauro C. X. Pinto; Jaime H. Amorim; Vasco A. C. Azevedo; Silma Regina Pereira; Alexandre Kanashiro; Fabio Cardoso Cruz; Rodrigo R. Resende; et al. (Stem Cell Reviews and Reports, 2023)

Ammonium removal characteristics of Delftia tsuruhatensis SDU2 with potential application in ammonium‑rich wastewater treatment - L. F. Chen; L. X. Chen; D. Pan; Y. L. Ren; J. Zhang; B. Zhou; J. Q. Lin; J. Q. Lin (International Journal of Environmental Science and Technology, 2023)

Long-term exposure to particulate matter and COPD mortality: Insights from causal inference methods based on a large population cohort in southern China - Ying Wang; Zhicheng Du; Yuqin Zhang; Shirui Chen; Shao Lin; Philip K. Hopke; David Q. Rich; Kai Zhang; Xiaobo X. Romeiko; Xinlei Deng; Yanji Qu; Yu Liu; et al. (Science of The Total Environment, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

Co-axial Projective Imaging for Augmented Reality Telementoring in Skin Cancer Surgery - Fan Zhang; Carlo M. Contreras; Pengfei Shao; Liping Zhao; Bingxuan Wu; Chenmeng Li; Feng Lin; Xiaohong Zhong; Zhongliang Lang; Peng Liu; Ronald X. Xu (Annals of Biomedical Engineering, 2022)

Correction: Co-axial Projective Imaging for Augmented Reality Telementoring in Skin Cancer Surgery - Fan Zhang; Carlo M. Contreras; Pengfei Shao; Liping Zhao; Bingxuan Wu; Chenmeng Li; Tao Lin; Xiaohong Zhong; Zhongliang Lang; Peng Liu; Ronald X. Xu (Annals of Biomedical Engineering, 2022)

Angiopoietin-Like Protein 4 Is Involved in Manganese Superoxide Dismutase-Mediated Suppression of Breast Cancer Cell Growth - P. Li; X. Zeng; Y. Liu; M. Lin (Bulletin of Experimental Biology and Medicine, 2022)

Delayed rFGF21 Administration Improves Cerebrovascular Remodeling and White Matter Repair After Focal Stroke in Diabetic Mice - Yinghua Jiang; Jinrui Han; Yadan Li; Yinga Wu; Ning Liu; Samuel X. Shi; Li Lin; Jing Yuan; Shusheng Wang; Ming-Ming Ning; Aaron S. Dumont; Xiaoying Wang (Translational Stroke Research, 2022)

Petrological and isotopic data from Eocene granites in the Luocang area, South Lhasa terrane, Tibet: implications for the India–Eurasia collision - J.-G. Gao; F. Ding; J.-Q. Lin; Q.-H. Zhu; Y. Sun; X.-G. Xie (Australian Journal of Earth Sciences, 2021)

Relative contributions of global warming, AMO and IPO to the land precipitation variabilities since 1930s - Li Tao; X. San Liang; Lin Cai; Jiuwei Zhao; Meng Zhang (Climate Dynamics, 2021)

Evaluation of favourable hot dry rock areas in the east of the Yishu fault zone in China - Q. Deng; A. Jiang; Z. Tong; H. Lin; Z. Gao; X. Sun; M. Nie (Australian Journal of Earth Sciences, 2021)

The stratigraphic significance of early Cambrian (Series 2, Stage 4) trilobites from the Smith Bay Shale near Freestone Creek, Kangaroo Island - J. B. Jago; C. J. Bentley; J. R. Paterson; J. D. Holmes; T. R. Lin; X. W. Sun (Australian Journal of Earth Sciences, 2021)

The Efficacy and Safety of Transcranial Direct Current Stimulation for Cerebellar Ataxia: a Systematic Review and Meta-Analysis - Tiffany X. Chen; Chen-Ya Yang; Gloria Willson; Chih-Chun Lin; Sheng-Han Kuo (The Cerebellum, 2021)

ERP evidence for asymmetric orthographic transfer between traditional and simplified Chinese - Jiushu Xie; Yanli Huang; Ke Chen; Qian Lin; John X. Zhang; Lei Mo (Experimental Brain Research, 2021)

The contrasting effects of thermodynamic and dynamic processes on East Asian summer monsoon precipitation during the Last Glacial Maximum: a data-model comparison - Yong Sun; Haibin Wu; Masa Kageyama; Gilles Ramstein; Laurent Z. X. Li; Ning Tan; Yating Lin; Bo Liu; Weipeng Zheng; Wenchao Zhang; Liwei Zou; Tianjun Zhou (Climate Dynamics, 2021)
The Last Glacial Maximum (LGM; 21 ka BP) was the most recent glacial period when the global ice sheet volume was at a maximum. Therefore, the LGM can be used to investigate atmospheric dynamics under a climate that differed significantly from the present. This study quantitatively compares pollen records of boreal summer (June–July–August) precipitation with the PMIP3 LGM simulations. The data-model comparison shows an overall agreement on a drier than pre-industrial East Asian summer monsoon (EASM) climate. Nevertheless, 17 out of 55 records show a regional precipitation increase that is also simulated over the additional land mass area due to sea level drop. The thermodynamic and dynamic responses are analyzed to explain a drier LGM EASM as a combination of these two antagonistic mechanisms. Relatively low atmospheric moisture content was the main thermodynamic control on the lower LGM (relative to pre-industrial levels) EASM precipitation amounts in both the reconstructions and the models. In contrast, two dynamic processes in relation to stationary eddy activity act to increase EASM precipitation regionally in records and simulations, respectively. Precipitation increase in records is explained by dynamic enhancement of the horizontal moisture transport, while dynamic enhancement of the vertical moisture transport leads to simulated precipitation increase over the specific region where landmass was exposed during LGM along continental coastlines of China due to significant drop in sea level (relative to pre-industrial levels). Overall, the opposing effects of thermodynamic and dynamic processes on precipitation during the LGM provide a means to reconcile the spatial heterogeneity of recorded precipitation changes in sign, although data-model comparison suggests that the simulated dynamic wetting mechanism is too weak relative to the thermodynamic drying mechanism over data-model disagreement regions.

Suitable plant combinations for ecological floating beds in eutrophic subtropical coastal wetlands under different salinities: experimental evidences - J. C. Lyu; G. H. Lin; Z. Y. Fan; W. X. Lin; Z. Dai (International Journal of Environmental Science and Technology, 2020)

Effect of Liposome-Encapsulated Zoledronic Acid on Microenvironment of Hepatocellular Carcinoma May Depend on the Ratio Between M1 and M2 Polarized Macrophages - S. Wu; X. Lin; X. Cui (Bulletin of Experimental Biology and Medicine, 2020)

Peripheral ProBDNF Delivered by an AAV Vector to the Muscle Triggers Depression-Like Behaviours in Mice - L. Y. Lin; S. Kelliny; L. C. Liu; M. Al-Hawwas; X. F. Zhou; L. Bobrovskaya (Neurotoxicity Research, 2020)

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

Effects of long-term planting on PhytOC storage and its distribution in soil physical fractions in Moso bamboo forests in subtropical China - Chengpeng Huang; Yongchun Li; Lin Jin; Xiaoqiang Gong; Jiasen Wu; Da Dong; Scott X. Chang; Peikun Jiang (Journal of Soils and Sediments, 2020)

Assessment of ammonium fertilization as a stimulus for proline accumulation in Oryza sativa L. during cyanide assimilation - W. Liu; X.-Z. Yu; S.-Y. Lei; L. Yang; Y.-J. Lin (International Journal of Environmental Science and Technology, 2020)

Accumulation and Transformation of 2,2',4,4'-Tetrabrominated Diphenyl Ether (BDE47) by the Earthworm Metaphire vulgaris in Soil - Yao Yao; Lin Wang; Philippe F.-X. Corvini; Rong Ji (Bulletin of Environmental Contamination and Toxicology, 2020)

Sedimentary environment and facies of the Huagang Formation in the northern central Xihu Depression, East China Sea Basin, China - Z. X. Zhao; C. M. Dong; C. Y. Lin; X. G. Zhang; X. Huang; B. J. Li; W. Guo; Z. Q. Zhu (Australian Journal of Earth Sciences, 2020)

A new slice-based method for calculating the minimum safe thickness for a filled-type karst cave - Z. H. Xu; X. Huang; S. C. Li; P. Lin; X. S. Shi; J. Wu (Bulletin of Engineering Geology and the Environment, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Characteristics and distribution of clay minerals and their effects on reservoir quality: Huagang Formation in the Xihu Sag, East China Sea Basin - X. L. Sun; C. Y. Lin; X. G. Zhang; J. L. Lin; Z. X. Zhao; D. W. Huang; D. P. Duan (Australian Journal of Earth Sciences, 2019)

Genome-wide Kdm4 histone demethylase transcriptional regulation in Drosophila - Amy Tsurumi; Shuang Xue; Lin Zhang; Jinghong Li; Willis X. Li (Molecular Genetics and Genomics, 2019)

The Long-Term Effects of Ethanol and Corticosterone on the Mood-Related Behaviours and the Balance Between Mature BDNF and proBDNF in Mice - L. Y. Lin; S. Y. Luo; M. Al-Hawwas; M. F. Herselman; X. F. Zhou; Larisa Bobrovskaya (Journal of Molecular Neuroscience, 2019)

Seasonal climatic effects and feedbacks of anthropogenic heat release due to global energy consumption with CAM5 - Bing Chen; C. Wu; X. Liu; L. Chen; Jian Wu; H. Yang; Tao Luo; Xue Wu; Yiquan Jiang; Lei Jiang; H. Y. Brown; Z. Lu; et al. (Climate Dynamics, 2019)

Cr-induced disturbance on expression of six COX genes in rice seedlings - X.-Z. Yu; C.-J. Lu; Y.-J. Lin; Y.-H. Li (International Journal of Environmental Science and Technology, 2019)

Exogenous and endogenous nitrogen differentially affect the decomposition of fine roots of different diameter classes of Mongolian pine in semi-arid northeast China - Qun Gang; Scott X. Chang; Guigang Lin; Qiong Zhao; Bing Mao; De-Hui Zeng (Plant and Soil, 2019)

Cover Image - X Luo; G Liao; C Liu; X Jiang; M Lin; C Zhao; J Tao; Z Huang (Journal of Fish Diseases, 2018)

Characterization of bacteriophage HN 48 and its protective effects in Nile tilapia Oreochromis niloticus against Streptococcus agalactiae infections - X Luo; G Liao; C Liu; X Jiang; M Lin; C Zhao; J Tao; Z Huang (Journal of Fish Diseases, 2018)
Streptococcus agalactiae is a causative agent responsible for massive mortalities of tilapia that has led to catastrophic losses to tilapia culture globally. Bacteriophages represent a new class of antimicrobials against bacteria. In this study, we characterized the bacteriophage HN 48, which formed small and round‐transparent plaques on a double‐layer plate. With a hexagonal head and a long tail, this phage may belong to the Caudovirales according to the International Committee on Taxonomy of Viruses. HN 48 was found to have a relatively wide and highly specific host range, to be sensitive to high temperature (60–80°C) and low pH (3–5), and to be relatively stable at alkaline pH (8–10). Intraperitoneal injection with HN 48 had no adverse effects on tilapia and effectively inactivated the bacteria in the kidney. Fish that received phage therapy had 60% ± 3.3% survival rates and a delayed mean death time of about 3 days when compared to the control group. To the best of knowledge, this is the first study of tilapia streptococcal phage. Overall, the results indicated that phage HN 48 could prevent tilapia from experimental S. agalactiae infection, suggesting it has the potential to control this disease.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Evaluating the interactions between surface water and groundwater in the arid mid-eastern Yanqi Basin, northwestern China - Ming Wu; Jianfeng Wu; Jin Lin; Xiaobin Zhu; Jichun Wu; Bill X. Hu (Hydrological Sciences Journal, 2018)

Converting natural evergreen broadleaf forests to intensively managed moso bamboo plantations affects the pool size and stability of soil organic carbon and enzyme activities - Ziwen Lin; Yongfu Li; Caixian Tang; Yu Luo; Weijun Fu; Xiaoqing Cai; Yongchun Li; Tian Yue; Peikun Jiang; Shuaidong Hu; Scott X. Chang (Biology and Fertility of Soils, 2018)

Linking muscle metabolism and functional variation to field swimming performance in bluegill sunfish (Lepomis macrochirus) - David J. Ellerby; Shauna Cyr; Angela X. Han; Mika Lin; Lloyd A. Trueblood (Journal of Comparative Physiology B, 2018)

Effect of electrode configurations on phytoremediation efficiency and environmental risk - Jie Luo; Lin Ye; Shihua Qi; Jian Wu; X. W. Sophie Gu (Plant and Soil, 2018)

Microbial dolomite in the sabkha environment of the middle Cambrian in the Tarim Basin, NW China - X. L. You; S. Sun; C. S. Lin; J. Q. Zhu (Australian Journal of Earth Sciences, 2018)

Design, synthesis, antitumor evaluation, 3D-QSAR and molecular docking studies of novel 4-aminoacridone compounds - Lin Tian; Chang J. Feng; Tong X. Li; Zhao Li; Wei H. Yang; Xiang E. Han (Medicinal Chemistry Research, 2017)

Development of In situ hybridization and real‐time PCR assays for the detection of Hepatospora eriocheir , a microsporidian pathogen in the Chinese mitten crab Eriocheir sinensis - Z F Ding; J Q Chen; J Lin; X S Zhu; G H Xu; R L Wang; Q G Meng; W Wang (Journal of Fish Diseases, 2017)
A microsporidian parasite, Hepatospora eriocheir , is an emerging pathogen for the Chinese mitten crab Eriocheir sinensis . Currently, there is scant information about the way it transmits infection in the crustacean of commercial importance, including its pathogenesis, propagation and infection route in vivo . In this study, chromogenic in situ hybridization ( ISH ) and quantitative real‐time PCR ( qPCR ) assays were developed to address this pressing need, and we provided an advance in the detection methods available. Pathogens can be seen in situ with associated lesions using ISH . Positive hybridization signals were noted inside the epithelial cells of the hepatopancreas, and putative free parasite spores were observed within the tubule lumen, which were associated with lesions detected by electron microscopy and haematoxylin and eosin (H&E) analysis. qPCR allows the determination of parasite loads in infected tissues, which is important for understanding disease progression and transmission. The hepatopancreas displayed the biggest statistical copy numbers among different tissues of infected crabs, confirming a tissue‐specific pathogen infection characteristic. The qPCR assay also proved to be suitable for the diagnosis of asymptomatic carrier crabs. Combination of the two methods could facilitate the study of H. eriocheir infection mechanism in E. sinensis , enhance the early diagnosis of the pathogen and improve the management of microsporidian diseases in commercial crustaceans.

Heat budget of the western Pacific warm pool and the contribution of eddy heat transport diagnosed from HYCOM assimilation - J. Chi; P. Shi; W. Zhuang; X. Lin; X. Cheng; Yan Du (Journal of Oceanography, 2017)

A bacterial infection by Vibrio harveyi causing heavy reduction of cultured lined seahorse Hippocampus erectus - G Qin; X Wang; S Tan; Q Lin (Journal of Fish Diseases, 2017)

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

Genetic Diversity of Populations of Saccharum spontaneum with Different Ploidy Levels Using SSR Molecular Markers - X. L. Liu; X. J. Li; C. H. Xu; X. Q. Lin; Z. H. Deng (Sugar Tech, 2016)

Differentiation in development of benzimidazole resistance in Colletotrichum gloeosporioides complex populations from strawberry and grape hosts - T. Lin; X. F. Xu; D. J. Dai; H. J. Shi; H. D. Wang; C. Q. Zhang (Australasian Plant Pathology, 2016)

A novel pathogenic bacteria ( Vibrio fortis ) causing enteritis in cultured seahorses, Hippocampus erectus Perry, 1810 - X Wang; Y Zhang; G Qin; W Luo; Q Lin (Journal of Fish Diseases, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Ecological Risk Assessment of EDTA-Assisted Phytoremediation of Cd Under Different Cultivation Systems - Jie Luo; Shihua Qi; X. W. Sophie Gu; Tao Hou; Lihong Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Histological analysis of somatic embryogenesis in pineapple: AcSERK1 and its expression validation under stress conditions - J. Ma; Y. H. He; Z. Y. Hu; S. Kanakala; W. T. Xu; J. X. Xia; C. H. Guo; S. Q. Lin; C. J. Chen; C. H. Wu; J. L. Zhang (Journal of Plant Biochemistry and Biotechnology, 2016)

Biodegradation of atrazine by Arthrobacter sp. C3, isolated from the herbicide-contaminated corn field - H. Wang; Y. Liu; J. Li; M. Lin; X. Hu (International Journal of Environmental Science and Technology, 2016)

Trends in land surface evapotranspiration across China with remotely sensed NDVI and climatological data for 1981–2010 - X. Mo; S. Liu; Z. Lin; S. Wang; S. Hu (Hydrological Sciences Journal, 2015)

Development and evaluation of a loop‐mediated isothermal amplification assay for the detection of channel catfish virus - G X Liu; L Lin; M Wang; X Q Liu (Journal of Fish Diseases, 2015)

Influence of Regional Difference in Bone Mineral Density on Hip Fracture Site in Elderly Females by Finite Element Analysis - Z. L. Lin; P. F. Li; Z. H. Pang; X. H. Zheng; F. Huang; H. H. Xu; Q. L. Li (Cell Biochemistry and Biophysics, 2015)

Roles of the Fibrous Superficial Zone in the Mechanical Behavior of TMJ Condylar Cartilage - Leonardo Ruggiero; Brandon K. Zimmerman; Miri Park; Lin Han; Liyun Wang; David L. Burris; X. Lucas Lu (Annals of Biomedical Engineering, 2015)

Rapid generation and analysis of expressed sequence tags to uncovering inflorescence secondary metabolism of Bougainvillea spectabilis ‘Speciosas’ by pyrosequencing - S. X. Xu; Q. Y. Huang; C. S. Lin; F. C. Lin; L. X. Lin; Q. Y. Shen (Euphytica, 2015)

Diversity and degradation mechanism of an anaerobic bacterial community treating phenolic wastewater with sulfate as an electron acceptor - X. J. Guo; Z. Y. Lu; P. Wang; H. Li; Z. Z. Huang; K. F. Lin; Y. D. Liu (Environmental Science and Pollution Research, 2015)

Neurology of the H1N1 pandemic in Singapore: a nationwide case series of children and adults - Asha Prerna; Jocelyn Y. X. Lim; Natalie W. H. Tan; Mas Suhaila Isa; Helen May-Lin Oh; Norazieda Yassin; Chian-Yong Low; Derrick W. S. Chan; Chia-Yin Chong; Yee-Sin Leo; Angela Li-Ping Chow; Paul Ananth Tambyah; et al. (Journal of NeuroVirology, 2015)

The juxtamembrane sequence of the Hepatitis C virus polymerase can affect RNA synthesis and inhibition by allosteric polymerase inhibitors - Y. Wen; X. Lin; B. Fan; C. T. Ranjith-Kumar; C. C. Kao (Virus Genes, 2015)

Infections of nervous necrosis virus in wild and cage‐reared marine fish from S outh C hina S ea with unexpected wide host ranges - X D Liu; J N Huang; S P Weng; X Q Hu; W J Chen; Z D Qin; X X Dong; X L Liu; Y Zhou; M Asim; W M Wang; J G He; et al. (Journal of Fish Diseases, 2015)
The concerns about the impact of the nervous necrosis virus ( NNV ) infections in wild fish have been raised. This paper presents the results of quarterly surveys of NNV in wild and cage‐reared marine fish from South China Sea. Samples of 892 wild fish belonging to 69 species and 381 cage‐reared fish belonging to 11 species were collected and were detected by seminested PCR and nested PCR . In the case of seminested PCR , the positive signal was detected in 3.0% and 3.1% samples of wild and cage‐reared fish, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 42.3% and 63.0% samples of wild and cage‐reared fish, respectively. If the fish species were considered, the positive signal was detected in 21.7% and 72.7% species of wild and cage‐reared fish by seminested PCR assay, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 65.2% and 100% species of wild and cage‐reared fish, respectively. The nucleotide sequences of the nested PCR products were determined. Phylogenetic tree showed that all the obtained viral isolates belonged to the red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype. Thirty‐five species of the marine fish were the new hosts of NNV .

Mass mortality associated with a viral‐induced anaemia in cage‐reared large yellow croaker, Larimichthys crocea (Richardson) - W J Xu; Z D Qin; H Shi; N Jiang; Y Zhou; X L Liu; J J Xie; G S Wang; W M Wang; M Asim; L B Zeng; L Lin (Journal of Fish Diseases, 2015)

Arsenic Accumulation in Panax notoginseng Monoculture and Intercropping with Pteris vittata - L. Y. Lin; X. L. Yan; X. Y. Liao; Y. X. Zhang; X. Ma (Water, Air, & Soil Pollution, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

Description of a New Species of the Genus Macromotettixoides Zheng (Orthoptera: Tetrigoidea: Metrodorinae) from China - W A Deng; C-L Lei; Z M Zheng; X D Li; L L Lin; M P Lin (Neotropical Entomology, 2014)

Wheat straw and its biochar had contrasting effects on soil C and N cycling two growing seasons after addition to a Black Chernozemic soil planted to barley - Ya-Lin Hu; Feng-Ping Wu; De-Hui Zeng; Scott X. Chang (Biology and Fertility of Soils, 2014)

Characterization of baseline sensitivity and resistance risk of Colletotrichum gloeosporioides complex isolates from strawberry and grape to two demethylation-inhibitor fungicides, prochloraz and tebuconazole - X. F. Xu; T. Lin; S. K. Yuan; D. J. Dai; H. J. Shi; C. Q. Zhang; H. D. Wang (Australasian Plant Pathology, 2014)

Comparison of flucytosine and fluconazole combined with amphotericin B for the treatment of HIV-associated cryptococcal meningitis: a systematic review and meta-analysis - Z.-W. Yao; X. Lu; C. Shen; D.-F. Lin (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Production GH transgenic goat improving mammogenesis by somatic cell nuclear transfer - Q. Zhang; J. Q. Chen; J. Lin; Q. H. Yu; H. Q. Yu; X. J. Xu; G. H. Liu; Q. Yang (Molecular Biology Reports, 2014)

Two New Species of the Genus Xistra Bolivar (Orthoptera: Tetrigidae) from China - X D Li; W A Deng; Z M Zheng; M P Lin; C W Lu (Neotropical Entomology, 2014)

Effects of Dietary Selenium Deficiency on mRNA Levels of Twenty-One Selenoprotein Genes in the Liver of Layer Chicken - C. P. Liu; J. Fu; S. L. Lin; X. S. Wang; S. Li (Biological Trace Element Research, 2014)

Evaluation of adsorption potential of bamboo biochar for metal-complex dye: equilibrium, kinetics and artificial neural network modeling - Y. Yang; X. Lin; B. Wei; Y. Zhao; J. Wang (International Journal of Environmental Science and Technology, 2014)

Soil nitrification and foliar δ15N declined with stand age in trembling aspen and jack pine forests in northern Alberta, Canada - Ya-Lin Hu; En-Rong Yan; Woo-Jung Choi; Francis Salifu; Xiao Tan; Z. Chi Chen; De-Hui Zeng; Scott X. Chang (Plant and Soil, 2014)

Haematopoietic necrosis of cultured Prussian carp, C arassius gibelio ( B loch), associated with C yprinid herpesvirus 2 - Y Z Luo; L Lin; Y Liu; Z X Wu; Z M Gu; L J Li; J F Yuan (Journal of Fish Diseases, 2013)

Effects of sub-chronic donepezil on brain Abeta and cognition in a mouse model of Alzheimer’s disease - Amy Easton; Sethu Sankaranarayanan; An Tanghe; Dick Terwel; Alan X. Lin; Nina Hoque; Clotilde Bourin; Huidong Gu; Michael Ahlijanian; Linda Bristow (Psychopharmacology, 2013)

Isolation and molecular analysis of genes Stpk-V2 and Stpk-V3 homologous to powdery mildew resistance gene Stpk-V in a Dasypyrum villosum accession and its derivatives - Z. S. Lin; Y. L. Zhang; M. J. Wang; J. R. Li; K. Wang; X. Chen; Q. F. Xu; X. S. Zhang; X. G. Ye (Journal of Applied Genetics, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

Dynamics of soil and root C stocks following afforestation of croplands with poplars in a semi-arid region in northeast China - Ya-Lin Hu; De-Hui Zeng; Scott X. Chang; Rong Mao (Plant and Soil, 2013)

Converting paddy fields to Lei bamboo (Phyllostachys praecox) stands affected soil nutrient concentrations, labile organic carbon pools, and organic carbon chemical compositions - Tao Zhang; Yongfu Li; Scott X. Chang; Peikun Jiang; Guomo Zhou; Juan Liu; Lin Lin (Plant and Soil, 2013)

A New Vector for Identification of Prokaryotes and Their Variable-Size Genomes - Tao Hou; Fu Liu; Caixia X. Lin; Dingyuan Y. Li (Current Microbiology, 2013)

Selenoprotein P and Yunnan Endemic Sudden Cardiac Death—an Ecological Study - Q. Li; X. Z. Li; T. Wang; L. W. Zhou; H. Q. Feng; L. Gao; J. R. Pei; C. Lin; C. X. Jiang (Biological Trace Element Research, 2013)

Effectiveness of soil N availability indices in predicting site productivity in the oil sands region of Alberta - En-Rong Yan; Ya-Lin Hu; Francis Salifu; Xiao Tan; Z. Chi Chen; Scott X. Chang (Plant and Soil, 2012)

Microbiologic characteristics of pathogenic bacteria from hospitalized trauma patients who survived Wenchuan earthquake - B. Zhang; Z. Liu; Z. Lin; X. Zhang; W. Fu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Phosphorus availability and rice grain yield in a paddy soil in response to long-term fertilization - Z. M. Lan; X. J. Lin; F. Wang; H. Zhang; C. R. Chen (Biology and Fertility of Soils, 2012)

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Immunoaffinity chromatography purification and ultra-high-performance liquid chromatography-tandem mass spectrometry determination of four β-agonists in beef - Q.-B. Lin; X.-T. Zhao; H. Song; Y.-L. Pan (Food Additives & Contaminants: Part A, 2012)

Arsenic content, fractionation, and ecological risk in the surface sediments of lake - S. L. Wang; C. Y. Lin; X. Z. Cao; X. Zhong (International Journal of Environmental Science and Technology, 2012)

First Isolation of Candida dubliniensis from Oral Cavities of Dermatological Patients in Nanjing, China - Yi P. Ge; Guo X. He; Tong Lin; Gui X. Lu; Yong N. Shen; Wei D. Liu (Mycopathologia, 2011)

In Vitro Toxicity Evaluation of 25-nm Anatase TiO2 Nanoparticles in Immortalized Keratinocyte Cells - Jin Chan; Tang Ying; Yang F. Guang; Li X. Lin; Tang Kai; Zhang Y. Fang; Ye X. Ting; Lin F. Xing; Yang Y. Ji (Biological Trace Element Research, 2011)

Cellular Toxicity of TiO2 Nanoparticles in Anatase and Rutile Crystal Phase - Chan Jin; Ying Tang; F. Guang Yang; X. Lin Li; Shan Xu; X. Yan Fan; Y. Ying Huang; Y. Ji Yang (Biological Trace Element Research, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

Inheritance of stripe rust resistance to predominant Chinese races in six spring wheat cultivars from the pacific Northwest of the United States - Y. Gao; Q. Sun; R. Wang; J. Feng; F. Lin; N. Cui; X. Chen; S. Xu; Y. Bai; X. Xu (Cereal Research Communications, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Long-term changes of dissolved oxygen, hypoxia, and the responses of the ecosystems in the East China Sea from 1975 to 1995 - X. Ning; C. Lin; J. Su; C. Liu; Q. Hao; F. Le (Journal of Oceanography, 2011)

Development of EST-PCR markers for Thinopyrum intermedium chromosome 2Ai#2 and their application in characterization of novel wheat-grass recombinants - M. J. Wang; Y. Zhang; Z. S. Lin; X. G. Ye; Y. P. Yuan; W. Ma; Z. Y. Xin (Theoretical and Applied Genetics, 2010)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Dopaminergic neurotoxicity following pulmonary exposure to manganese-containing welding fumes - Krishnan Sriram; Gary X. Lin; Amy M. Jefferson; Jenny R. Roberts; Rebecca S. Chapman; Bean T. Chen; Joleen M. Soukup; Andrew J. Ghio; James M. Antonini (Archives of Toxicology, 2010)

In vitro propagation of four threatened Paphiopedilum species (Orchidaceae) - Bo Long; Alex X. Niemiera; Zhi-ying Cheng; Chun-lin Long (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Organic mulch and fertilization affect soil carbon pools and forms under intensively managed bamboo (Phyllostachys praecox) forests in southeast China - Yongfu Li; Peikun Jiang; Scott X. Chang; Jiasen Wu; Lin Lin (Journal of Soils and Sediments, 2010)

Occurrence of Aliphatic Hydrocarbons in Water, Suspended Particulate Matter and Sediments of Daliao River System, China - W. Guo; M. C. He; Z. F. Yang; C. Y. Lin; X. C. Quan (Bulletin of Environmental Contamination and Toxicology, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Hepsin activates prostasin and cleaves the extracellular domain of the epidermal growth factor receptor - Mengqian Chen; Li-Mei Chen; Chen-Yong Lin; Karl X. Chai (Molecular and Cellular Biochemistry, 2010)

A storm event-based approach to TMDL development - Tsung-Hung Hsu; Jen-Yang Lin; Tsu-Chuan Lee; Harry X. Zhang; Shaw L. Yu (Environmental Monitoring and Assessment, 2010)

Effects of two species of inorganic arsenic on the nutrient physiology of rice seedlings - Hai Bin Wang; H. B. He; G. D. Yang; C. Y. Ye; B. H. Niu; W. X. Lin (Acta Physiologiae Plantarum, 2010)

The delayed response of Toll-like receptors may relate to Pseudomonas aeruginosa keratitis exacerbating rapidly at the early stages of infection - X. Jin; Z. Lin; X. Xie (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Seroprevalence of Toxoplasma gondii infection in breeding sows in Western Fujian Province, China - C. Q. Huang; Y. Y. Lin; A. L. Dai; X. H. Li; X. Y. Yang; Z. G. Yuan; X. Q. Zhu (Tropical Animal Health and Production, 2010)

Genetic variation in colchicine-treated regenerated plants of Eucalyptus globulus Labill. - X. Z. Liu; H. Lin; X. Y. Mo; T. Long; H. Y. Zhang (Journal of Genetics, 2009)

Transpositional activation of mPing in an asymmetric nuclear somatic cell hybrid of rice and Zizania latifolia was accompanied by massive element loss - X. H. Shan; X. F. Ou; Z. L. Liu; Y. Z. Dong; X. Y. Lin; X. W. Li; B. Liu (Theoretical and Applied Genetics, 2009)

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

Effect of polymorphism in the leukemia inhibitory factor gene on litter size in Large White pigs - H. C. Lin; G. F. Liu; A. G. Wang; L. J. Kong; X. F. Wang; J. L. Fu (Molecular Biology Reports, 2009)

Variability of total and available copper concentrations in relation to land use and soil properties in Yangtze River Delta of China - Xiuying Zhang; Fenfang Lin; Yugen Jiang; Ke Wang; X. L. Feng (Environmental Monitoring and Assessment, 2009)

Study on the Relationship Between Meteorological Conditions and Acid Rain in Mid-Eastern Fujian - C. C. Lin; J. X. Liu; Y. Y. Cai; B. L. Li; Z. L. Wang; B. B. Chen (Bulletin of Environmental Contamination and Toxicology, 2009)

Identification of soil heavy metal sources from anthropogenic activities and pollution assessment of Fuyang County, China - X. Y. Zhang; F. F. Lin; Mike T. F. Wong; X. L. Feng; K. Wang (Environmental Monitoring and Assessment, 2009)

The Impact of Iodine Excess on Thyroid Hormone Biosynthesis and Metabolism in Rats - K. Wang; Y. N. Sun; J. Y. Liu; L. Zhang; Y. Ye; L. X. Lin; Y. Q. Yan; Z. P. Chen (Biological Trace Element Research, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

The occurrence of the feline “Candidatus Mycoplasma haemominutum” in dog in China confirmed by sequence-based analysis of ribosomal DNA - Q. J. Zhuang; H. J. Zhang; R. Q. Lin; M. F. Sun; X. J. Liang; X. W. Qin; W. J. Pu; X. Q. Zhu (Tropical Animal Health and Production, 2009)

Prevalence of helminths in water buffaloes in Hunan Province, China - Y. Liu; F. Li; W. Liu; R. S. Dai; Y. M. Tan; D. S. He; R. Q. Lin; X. Q. Zhu (Tropical Animal Health and Production, 2009)

A quick and efficient approach for gene silencing by using triple putative microRNA-based short hairpin RNAs - Z. X. Shan; Q. X. Lin; M. Yang; C. Y. Deng; S. J. Kuang; Z. L. Zhou; D. Z. Xiao; X. Y. Liu; S. G. Lin; X. Y. Yu (Molecular and Cellular Biochemistry, 2009)

Quantitative trait loci for non-race-specific, high-temperature adult-plant resistance to stripe rust in wheat cultivar Express - F. Lin; X. M. Chen (Theoretical and Applied Genetics, 2009)

Identification of wheat line YW243 on comprehensive resistance to several diseases by pathogens and molecular markers - H. Xie; Z. Lin; Z. Zhang; L. Du; Z. Xin; Y. Ma; X. Ye; X. Chen (Cereal Research Communications, 2008)

New insights into the role of angiotensin-converting enzyme obtained from the analysis of genetically modified mice - Xiao Z. Shen; Hong D. Xiao; Ping Li; Chentao X. Lin; Sandrine Billet; Derick Okwan-Duodu; Jon W. Adams; Ellen A. Bernstein; Yi Xu; Sebastien Fuchs; Kenneth E. Bernstein (Journal of Molecular Medicine, 2008)

Sensitivity of future ozone concentrations in the northeast USA to regional climate change - K. E. Kunkel; H.-C. Huang; X.-Z. Liang; J.-T. Lin; D. Wuebbles; Z. Tao; A. Williams; M. Caughey; J. Zhu; K. Hayhoe (Mitigation and Adaptation Strategies for Global Change, 2008)

Molecular mapping of genes for race-specific overall resistance to stripe rust in wheat cultivar Express - F. Lin; X. M. Chen (Theoretical and Applied Genetics, 2008)

Expression and immunogenic comparison of VP2 and VP3 from marine birnavirus - H‐J Xu; J‐G Lin; C‐X Zhang; S Suzuki (Journal of Fish Diseases, 2008)
The coding regions for the major epitopes of structural protein VP2 ( vp2e ) and structural protein VP3 were amplified from marine birnavirus (MABV) cDNA and efficiently expressed as glutathione S‐transferase (GST) fusion proteins in Escherichia coli . Polyclonal antibodies against VP2e and VP3 were raised in rabbits and fish using the purified proteins of GST/VP2e and GST/VP3. The rabbit anti‐serum against VP3 was more sensitive than the rabbit anti‐VP2e serum in detecting virus in MABV‐infected fish, while fish anti‐VP2e serum showed a stronger neutralization response than fish anti‐VP3 serum.

What are daily maximum and minimum temperatures in observed climatology? - X. Lin; K. G. Hubbard (International Journal of Climatology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Endosperm-specific hypomethylation, and meiotic inheritance and variation of DNA methylation level and pattern in sorghum (Sorghum bicolor L.) inter-strain hybrids - M. S. Zhang; H. Y. Yan; N. Zhao; X. Y. Lin; J. S. Pang; K. Z. Xu; L. X. Liu; B. Liu (Theoretical and Applied Genetics, 2007)

Livestock Odour Dispersion as Affected by Natural Windbreaks - X.-J. Lin; S. Barrington; J. Nicell; D. Choinière; S. King (Water, Air, & Soil Pollution, 2007)

Accumulation of additive effects generates a strong photoperiod sensitivity in the extremely late-heading rice cultivar ‘Nona Bokra’ - Y. Uga; Y. Nonoue; Z. W. Liang; H. X. Lin; S. Yamamoto; U. Yamanouchi; M. Yano (Theoretical and Applied Genetics, 2007)

Soil Nutrient Load and Drain Water Quality in Seepage Fields Receiving Milk House Wastewater - S. Morin; J. K. Whalen; S. Barrington; X. Lin (Water, Air, & Soil Pollution, 2007)

Genetics and molecular mapping of genes for race-specific all-stage resistance and non-race-specific high-temperature adult-plant resistance to stripe rust in spring wheat cultivar Alpowa - F. Lin; X. M. Chen (Theoretical and Applied Genetics, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

Isolation of Endophytic Actinomycetes from Different Cultivars of Tomato and their Activities Against Ralstonia solanacearum in Vitro - H. M. Tan; L. X. Cao; Z. F. He; G. J. Su; B. Lin; S. N. Zhou (World Journal of Microbiology and Biotechnology, 2006)

Detection of Hong Kong 97-like H5N1 influenza viruses from eggs of Vietnamese waterfowl - Y. Li; Z. Lin; J. Shi; Q. Qi; G. Deng; Z. Li; X. Wang; G. Tian; H. Chen (Archives of Virology, 2006)

Extent and pattern of DNA methylation alteration in rice lines derived from introgressive hybridization of rice and Zizania latifolia Griseb - Z. Y. Dong; Y. M. Wang; Z. J. Zhang; Y. Shen; X. Y. Lin; X. F. Ou; F. P. Han; B. Liu (Theoretical and Applied Genetics, 2006)

Ancient paddy soils from the Neolithic age in China’s Yangtze River Delta - Z. H. Cao; J. L. Ding; Z. Y. Hu; H. Knicker; I. Kögel-Knabner; L. Z. Yang; R. Yin; X. G. Lin; Y. H. Dong (The Science of Nature, 2006)

Renoprotective effects of combination of angiotensin converting enzyme inhibitor with mycophenolate mofetil in diabetic rats - Y. -G. Wu; H. Lin; H Qian; M. Zhao; X. -M. Qi; G. -Z. Wu; S. -T. Lin (Inflammation Research, 2006)

Protoplast electrofusion between common wheat (Triticum aestivum L.) and Italian ryegrass (Lolium multiflorum Lam.) and regeneration of mature cybrids - T. M. Ge; X. H. Lin; F. L. Qin; S. W. Yu; Y. J. Yu (In Vitro Cellular & Developmental Biology - Plant, 2006)

Neuromodulation in the Spiral Ganglion: Shaping Signals from the Organ of Corti to the CNS - D. Dulon; D.J. Jagger; X. Lin; R.L. Davis (The Journal of Membrane Biology, 2006)

Probability density estimation in stochastic environmental models using reverse representations - E. van den. Berg; A. W. Heemink; H. X. Lin; J. G. M. Schoenmakers (Stochastic Environmental Research and Risk Assessment, 2006)

The influence of bridging ligand electronic structure on the photophysical properties of noble metal diimine and triimine light harvesting systems - Xian-yong Wang; Andre Del Guerzo; Sujoy Baitalik; Gerald Simon; George B. Shaw; Lin X. Chen; Russell Schmehl (Photosynthesis Research, 2006)

Genetic and physical mapping of Pi36(t), a novel rice blast resistance gene located on rice chromosome 8 - X. Q. Liu; L. Wang; S. Chen; F. Lin; Q. H. Pan (Molecular Genetics and Genomics, 2005)

Regional trends in recent precipitation indices in China - W. Qian; X. Lin (Meteorology and Atmospheric Physics, 2005)

Isolation and characterization of actinomycetes antagonistic to pathogenic Vibrio spp. from nearshore marine sediments - J. L. You; L. X. Cao; G. F. Liu; S. N. Zhou; H. M. Tan; Y. C. Lin (World Journal of Microbiology and Biotechnology, 2005)

Surface air temperature records biased by snow-covered surface - X. Lin; K. G. Hubbard; C. B. Baker (International Journal of Climatology, 2005)

Mining the structural knowledge of high-dimensional medical data using isomap - S. Weng; C. Zhang; Z. Lin; X. Zhang (Medical & Biological Engineering & Computing, 2005)

Manganese Uptake and Accumulation by Two Populations of Phytolacca acinosa Roxb. (Phytolaccaceae) - S. G. Xue; Y. X. CHEN; A. J. M. Baker; R. D. Reeves; X. H. Xu; Q. Lin (Water, Air, & Soil Pollution, 2005)

Further molecular characterisation of potyviruses infecting aroid plants for medicinal use in China - Y.-H. Shi; X.-Y. Hong; J. Chen; M. J. Adams; H.-Y. Zheng; L. Lin; B.-X. Qin; J.-P. Chen (Archives of Virology, 2005)

Mapping QTL associated with resistance to Fusarium head blight in the Nanda2419נWangshuibai population. I. TypeII resistance - F. Lin; Z. X. Kong; H. L. Zhu; S. L. Xue; J. Z. Wu; D. G. Tian; J. B. Wei; C. Q. Zhang; Z. Q. Ma (Theoretical and Applied Genetics, 2004)

Identification of a 98-kb DNA segment containing the rice Eui gene controlling uppermost internode elongation, and construction of a TAC transgene sublibrary - Y.-H. Xu; Y.-Y. Zhu; H.-C. Zhou; Q. Li; Z.-X. Sun; Y.-G. Liu; H.-X. Lin; Z.-H. He (Molecular Genetics and Genomics, 2004)

A likelihood approach for mapping growth trajectories using dominant markers in a phase-unknown full-sib family - C.-X. Ma; M. Lin; R. C. Littell; T. Yin; R. Wu (Theoretical and Applied Genetics, 2004)

QTLs for Na+ and K+ uptake of the shoots and roots controlling rice salt tolerance - H. X. Lin; M. Z. Zhu; M. Yano; J. P. Gao; Z. W. Liang; W. A. Su; X. H. Hu; Z. H. Ren; D. Y. Chao (Theoretical and Applied Genetics, 2004)

Application of a ?Big-Tree? model to regional climate modeling: a sensitivity study - X.-M. Zeng; M. Zhao; R.-C. Yu; N.-S. Lin; Y.-Q. Zheng; L.-J. Zhang; R.-J. Zhang (Theoretical and Applied Climatology, 2003)

Cloning and characterization of leaf cDNAs that are differentially expressed between wheat hybrids and their parents - L. M. Wu; Z. F. Ni; F. R. Meng; Z. Lin; Q. X. Sun (Molecular Genetics and Genomics, 2003)

Outbreaks of an iridovirus disease in maricultured large yellow croaker, Larimichthys crocea (Richardson), in China - X H Chen; K B Lin; X W Wang (Journal of Fish Diseases, 2003)

A framework for integrating the songbird brain - Jarvis E.; Smith V.; Wada K.; Rivas M.; McElroy M.; Smulders T.; Carninci P.; Hayashizaki Y.; Dietrich F.; Wu X.; McConnell P.; Yu J.; et al. (Journal of Comparative Physiology A, 2002)

Elevated atmospheric CO 2 alters wood production, wood quality and wood strength of Scots pine ( Pinus sylvestris L) after three years of enrichment - R. Ceulemans; M. E. Jach; R. Van De Velde; J. X. Lin; M. Stevens (Global Change Biology, 2002)
Scots pine ( Pinus sylvestris L.) trees were grown in open top chambers for three years under ambient and elevated CO 2 concentrations. The trees were aged 3 y at the beginning of the CO 2 exposure, and the effects of the treatment on total stem volume, stem wood biomass, wood quality and wood anatomy were examined at the end of the exposure. The elevated CO 2 treatment lead to a 49% and 38% increase in stem biomass and stem wood volume, respectively. However, no significant effects of the elevated CO 2 treatment on wood density were observed, neither when green wood density was estimated from stem biomass and stem volume, nor when oven‐dry wood density was measured on small wood samples. Under elevated CO 2 significantly wider growth rings were observed. The effect of elevated CO 2 on growth ring width was primarily the result of an increase in earlywood width. Wood compression strength decreased under elevated CO 2 conditions, which could be explained by significantly larger tracheids and the increased earlywood band, that has thinner walls and larger cavities. A significant decrease of the number of resin canals in the third growth ring was observed under the elevated treatment; this might indicate that trees produced and contained less resin, which has implications for disease and pest resistance. So, although wood volume yield in Scots pine increased significantly with elevated CO 2 after three years of treatment, wood density remained unchanged, while wood strength decreased. Whilst wood volume and stem biomass production may increase in this major boreal forest tree species, wood quality and resin production might decrease under future elevated CO 2 conditions.

Thallium Concentration in Lake Trout from Lake Michigan - T.-S. Lin; J. Nriagu; X.-Q. Wang (Bulletin of Environmental Contamination and Toxicology, 2001)

A natural-gradient field tracer test for evaluation of pollutant-transport parameters in a porous-medium aquifer - Y. Yang; X. Lin; T. Elliot; R. Kalin (Hydrogeology Journal, 2001)

Development and characterization of common wheat-Thinopyrum intermedium translocation lines with resistance to barley yellow dwarf virus - Z.Y. Xin; Z.Y. Zhang; X. Chen; Z.S. Lin; Y.Z. Ma; H.J. Xu; P.M. Banks; P.J. Larkin (Euphytica, 2001)

Antibody responses to respiratory coronavirus infections of cattle during shipping fever pathogenesis - X. Q. Lin; K. L. O’Reilly; J. Storz; C. W. Purdy; R. W. Loan (Archives of Virology, 2000)

Characterization and detection of epistatic interactions of 3 QTLs, Hd1, Hd2, and Hd3, controlling heading date in rice using nearly isogenic lines - H. X. Lin; T. Yamamoto; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2000)

Soil Leaching Column Chromatographic Technique for Estimation of Leaching Behavior of Atrazine, Deethylatrazine, Deisopropylatrazine, and Hydroxyatrazine on Soil - F. Xu *, , X.-M. Liang; B. Lin; F. Su; H. Zhong; K.-W. Schramm; A. Kettrup (Bulletin of Environmental Contamination and Toxicology, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Transgenic peppermint ( Mentha × piperita L.) plants obtained by cocultivation with Agrobacterium tumefaciens - X. Niu; K. Lin; P. M. Hasegawa; R. A. Bressan; S. C. Weller (Plant Cell Reports, 1998)

Estimation of myocardial glucose utilisation with PET using the left ventricular time-activity curve as a non-invasive input function - X. Li; D. Feng; K. -P. Lin; S. -C. Huang (Medical & Biological Engineering & Computing, 1998)

Analysis of QTL×environment interaction for yield components and plant height in rice - J.-Y. Zhuang; H.-X. Lin; J. Lu; H.-R. Qian; S. Hittalmani; N. Huang; K.-L. Zheng (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Identifying different types of de-differentiated microspores from indica-japonica F1 hybrids with subspecies-differentiating RFLP probes in rice - J. -H. Xie; M. -W. Gao; J. Lu; J. -Y. Zhuang; H. -X. Lin; H. -R. Qian; K. -L. Zheng (Theoretical and Applied Genetics, 1997)

Deletion of the carboxy-terminus of herpes simplex virus type 1 (HSV-1) glycoprotein B does not affect oligomerization, heparin-binding activity, or its ability to protect against HSV challenge - X. H. Lin; M. A. Ali; H. Openshaw; E. M. Cantin (Archives of Virology, 1996)

A new immunostimulatory complex (PICKCa) in experimental rabies: antiviral and adjuvant effects - H. X. Lin; C. Gontier; M-F. Saron; P. Perrin (Archives of Virology, 1993)

Stimulation of thymidine kinase activity in baculovirus infected cells is not due to a virus-coded enzyme - X. Wang; W. Xie; Q. Long; D. He; G. Lin; Y. Pang; Z. Pu (Archives of Virology, 1992)